FENOMENOLOGI IBU BEKERJA DALAM PEMBERIAN ASI EKSKLUSIF DI RSU IMELDA MEDAN - Bernita Silalahi; Fronika Harahap; Paskah Rina; Meriani Herlina; Noradina Noradina; Arta Marisi Dame (Jurnal Ilmiah Keperawatan IMELDA, 2026)
Exclusive breastfeeding is the provision of breast milk for the first 6 months of a baby's life without other food or drink except vitamins, medicines and oralit. The function of breast milk is to meet the baby's nutritional intake, strengthen the immune system, and reduce infant mortality and morbidity. The purpose of this study was to determine the Experience of Working Mothers in Providing Exclusive Breast Milk at the Imelda Buruh Indonesia General Hospital, Medan. The research method used is a qualitative research type with a descriptive phenomenological approach. The location of this research was carried out at the Imelda Buruh Indonesia General Hospital, Medan. The time of this research was carried out from March to August 2024. The number of participants in this study was 5 people. Research data were collected through in-depth interviews with participants and analyzed thematically. The results of the study consisted of 4 themes, namely: 1 (Working Mothers' Anxiety regarding the Fulfillment of Exclusive Breast Milk for Babies), 2 (Practices and Strategies in Pumping and Storing Breast Milk for Working Mothers), 3 (Support from Husband and Family in the Success of Working Mothers in Providing Exclusive Breast Milk), 4 (Benefits of Breast Milk for Maternal and Infant Health). The conclusion of this study shows that working mothers face various challenges in ensuring exclusive breastfeeding for their babies, especially related to concerns about the schedule and quality of breast milk, breast milk management, and the important role of family support. Consistency in breast milk expression scheduling and appropriate storage strategies are essential to maintain adequate breast milk supply. In addition, support from husbands and families, as well as supporting facilities at the workplace, play an important role in the success of exclusive breastfeeding, which has a significant positive impact on maternal and infant health.